Financial Viability Assessment of Koi (Cyprinus Rubrofuscus) Culture Through Selective Breeding Programs : A Case Study of Indonesian Commercial Koi Farms - Fauzan, Agung Luthfi; Ramadhana, Ahnadia Wulan; Dewi, Nina Nurmalia (Jurnal Media Akuakultur Indonesia, 2025)
This study aims to evaluate the financial performance of the koi fish farming industry (Cyprinus rubrofuscus) in Indonesia through a selective breeding program. Data collected between 2021 and 2024, covering business development, operational costs, investment costs, and capital estimates, was obtained from 24 koi fish farming businesses in the Java region. Businesses using genetic screening aim to reduce financial disparities, which is different from traditional aquaculture methods. The analysis's results indicate that the implementation of the selective breeding program in a scientific manner yielded a higher profit margin of 34.2% than the traditional method, which only reached 18.7%. Although the initial investment is more substantial (about Rp28,5 million per hectare), the time frame required to pay for the investment is more efficient, i.e., between 18 and 24 months. The price of koi fish is higher than the market price, possibly reaching 2.8% of the price of koi fish, with the selling price per tail ranging from Rp450,000 to Rp1,200,000. In addition, there was a 15% increase in feed efficiency and a 3% decrease in mortality, which means a 7.8% reduction. Thus, this selective breeding program can improve koi farming production and sales performance by applying genetic technology, which can help overcome the financial crisis in the aquaculture sector in developing countries.